2008
DOI: 10.1002/ddr.20223
|View full text |Cite
|
Sign up to set email alerts
|

Drug design: hiding in full view

Abstract: Compounds that can produce potent biological effects in cells encompass a variety of structural motifs. Many of these compounds share a structural feature that has rarely been noted. It is an allylic cluster of atoms, a 3-carbon chain with a double bond between two of the atoms and an oxygen atom at the other end. The oxygen can be in a hydroxyl group, or in an ether or ketal or ester linkage, or simply a carbonyl form. In the latter case, the linkage is an allylic ketone (ene-one) structure. Nitrogen is often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Second, a recent review indicated that many bioactive compounds contain an allylic group with an oxygen atom at one end of this substituent [82]. The oxygen atom can be located in a hydroxy, ester, ether, ketal or carbonyl substituents.…”
Section: Concluding Remarks On Cytotoxicitymentioning
confidence: 99%
“…Second, a recent review indicated that many bioactive compounds contain an allylic group with an oxygen atom at one end of this substituent [82]. The oxygen atom can be located in a hydroxy, ester, ether, ketal or carbonyl substituents.…”
Section: Concluding Remarks On Cytotoxicitymentioning
confidence: 99%
“…The importance of the vinylation reactions of ketones stems not only from frequent appearance of the C–C double bond-carbonyl entities in natural products and biologically active compounds but also from the rich and well-studied chemistry of β,γ-unsaturated ketones that enables expedient synthesis of complex structures . Many synthetic approaches to β,γ-unsaturated ketones have been documented.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the vinylation reactions of ketones stems not only from the frequent appearance of the C=C bond carbonyl entities in natural products and biologically active compounds, 2 but also from the rich and well-studied chemistry of β,γ-unsaturated ketones 3 that enables expedient synthesis of complex structures. 4 Promising synthetic building blocks are also intermediates of this reaction, for example, dienolate 3, which may be C-and O-alkylated in situ and participate in Diels-Alder synthesis as well as form various heterocyclic compounds attaching different binucleophiles.…”
Section: Scheme 1 Addition Of Ketones 1 To Alkynes 2 In Superbasic Mediamentioning
confidence: 99%